Energy performance and profitability of biomass boilers in commercial sector: the case study of Sainsbury's stores in the UK. (August 2018) - Sorrentino, Arianna; Pantaleo, Antonio M.; Markides, Christos N.; Braccio, Giacobbe; Fanelli, Emanuele; Camporeale, Sergio M
Abstract: Commercial buildings or shopping malls are characterized by large thermal and electrical energy consumptions with high variability of energy demand. Therefore, there is a large interest to explore novel renewable energy generation systems for these applications. A novel flexible configuration of biomass-fired CHP system with organic Rankine cycle (ORC) is here proposed and applied to the case study of Sainsbury's supermarkets in the UK. The proposed configuration adopts a molten salt (MS) circuit to transfer heat from the biomass furnace to the ORC plant. A thermal Energy Storage (TES) is proposed to improve the flexible operation of the plant and reduce the size of the biomass boiler. Molten salts have been preferred to thermal oil as they have no fire risks and low environmental impact and can be used as medium for a Two Tank TES with a "direct heating" scheme. The plant has been analysed using real input data of biomass boiler installed, conversion efficiency and heat demand from the store. The model is informed by hourly energy costs and electricity feed in tariff in order to define optimal size and operation of the bottoming ORC for the specific case study of large commercial energy end user in the UK. The results show that the use of thermal storage in a biomass-fired ORC plant can improve the boiler efficiency and reduce the biomass consumption in thermal-load following operating mode and increase the investment profitability.